The concept of 'agroenergy district': a relevant tool for sustainable development in rural areas - Julien Frayssignes (European Regional Science Association (ERSA), 2011)
Our proposal is linked with an European cooperation project bound to Mediterranean agriculture. The paper aims to develop a partially renewed approach of the district concept as a development model for rural areas, applied to the organization of the agroenergy sector. Originally developed by Marshall, the concept of district was reactualized by Italian researchers in the 70's (Beccatini). In France, the concept of Industrialized Productive System was notably developed by Courlet and Pecqueur (1992) to analyse local dynamics of development based on the cooperation between small firms, R&D institutions and public local authorities. Our paper aims to discuss the relevance of the concept of district in the implementation of an agroenergy activity at local scale: -to what extent this concept can contribute to strengthen the collective capacity of local stakeholders? (organization of an agroenergy chain), -to what extent the concept can bring answers to stakes bound to agroenergy sector? (competitivity of rural areas, employment, farmers income, preservation of natural resources, climate change, cohesion and standard of living), -to what extent the concept can encourage a development based on local resource valuation (spatial and social proximity between stakeholders) and avoid the drifts bound to competition between food and agroenergy productions? In this perspective, the ambition of the paper is also to illustrate the territorial anchoring of an agroenergy district, in particular through: -the Mediterranean dimensions of the regions involved in the project (natural and social aspects), -the public policies supporting agroenergy sector, and notably the role of regional institutions in the implementation of such districts. This analysis will bring us to mobilize the theoretical model of territorial footing developed during our Ph.D in Geography dedicated to the link between origin labeled products and rural development. Finally, the objective is to promote an operational methodology able to help local actors to implement a Sustainable Mediterranean Agroenergy District (SMAD). This initiative is an opportunity for the development of rural areas and the elaboration of agroenergy strategies able to conform to the sustainability criteria evoked in the European directive bound to renewable energies.
Keywords: 330